Direct diffeomorphic reparameterization for correspondence optimization in statistical shape modeling. (July 2015) - Li, Kang; Qian, Xiaoping
Abstract: In this paper, we propose an efficient optimization approach for obtaining shape correspondence across a group of objects for statistical shape modeling. With each shape represented in a B-spline based parametric form, the correspondence across the shape population is cast as an issue of seeking a reparameterization for each shape so that a quality measure of the resulting shape correspondence across the group is optimized. The quality measure is the description length of the covariance matrix of the shape population, with landmarks sampled on each shape. The movement of landmarks on each B-spline shape is controlled by the reparameterization of the B-spline shape. The reparameterization itself is also represented with B-splines and B-spline coefficients are used as optimization parameters. We have developed formulations for ensuring the bijectivity of the reparameterization. A gradient-based optimization approach is developed, including techniques such as constraint aggregation and adjoint sensitivity for efficient, direct diffeomorphic reparameterization of landmarks to improve the group-wise shape correspondence. Numerical experiments on both synthetic and real 2D and 3D data sets demonstrate the efficiency and effectiveness of the proposed approach. Highlights: We propose an approach for optimizing shape correspondence across a population. B-splines are used for shape representation and reparameterization. The quality measure of the statistical shape model is the description length. An adjoint method for deriving analytical sensitivity is developed. The approach improves shape correspondence in a group-wise manner.